Politics of internationalisation and the migration-higher education nexus. (15th March 2023) - Cerna, Lucie; Chou, Meng-Hsuan
ABSTRACT: Taking the migration-higher education nexus as an analytical entry point, we address the question: How can we account for different internationalisation outcomes? We focus on three actors involved in the global race to internationalise higher education activities: higher education institutions (HEIs), states, and migrants. We argue that the migration-higher education nexus enables us to begin describing and explaining differences in internationalisation outcomes (i.e. greater, limited, or none) by focussing our empirical attention on the interaction between HEI internationalisation strategies, state policies, and migrant agency to move/stay. We delineate various configurations of these interactions and how they determine internationalisation outcomes.